Do the competencies of tax accounting students meet the skills required in the Industry 4.0 era? - Frida Magda Sumual; Frandy Efraim Fritz Karundeng (Universitas Hayam Wuruk Perbanas, 2024)
In this Industry 4.0 era, many college graduates are unemployed because they do not have the competencies that suit the company’s needs. In addition, companies in the Industry 4.0 era also require workers to master the internet and technology because in this era all company business operations are automated. The accounting profession, including the tax accounting profession, has also adapted to developments in technology and the internet in carrying out its duties. Accounting students are required to be able to adapt their taxation capabilities and digital skills to the needs of companies in the Industry 4.0 era. This research is descriptive qualitative research with secondary data sourced from various literature, especially job vacancy advertisements, and primary data in the form of interviews with accounting students. The results of the analysis show that companies in the Industry 4.0 era require students to master basic skills in taxation, especially those related to Income Tax, digital tax applications issued by the Directorate General of Taxes, and data processing applications, such as Ms. Excel, and accounting applications, for example Accurate and Odoo. In general, the accounting study program curriculum is in line with company needs, but there needs to be more training programs for tax practices and accounting computer applications.